Presence of Varroa destructor, Nosema spp. and Acarapis woodi in colonies of bees from Tabasco, Mexico - Martínez Puc, Jesús Froylán; Gómez Leyva, Juan Florencio; González Cortés, Nicolás; Catzím Rojas, Francisco Javier; Sánchez Melo, Yessenia; Payró de la Cruz, Emeterio (Revista Mexicana de Ciencias Agrícolas, 2022)
Bee (Apis mellifera) diseases cause great economic losses and are considered the main cause of the high loss of colonies. In this study, the frequency and infestation levels of Varroa destructor and Acarapis woodi were determined. Likewise, the frequency and infection levels of Nosema spp. in colonies of honeybees from Tabasco, Mexico, were determined. During October to November 2020, bee samples were collected in 112 colonies in the five subregions of Tabasco. The frequency and levels of infestation of V. destructor were diagnosed using the capped brood comb fragment technique, as well as the washing of adult bees. The quantification of spores of Nosema spp. was performed by macerating abdomens and visual identification of A. woodi in tracheas using a stereoscopic microscope. At the state level, it was found a frequency of V. destructor in capped brood (FVCO)= 69.64%; level of infestation of V. destructor in capped brood (NIVCO)= 13.86% (p= 0.419), likewise, it was observed a frequency of V. destructor in adult bees (FVAA)= 92.86%; level of infestation of V. destructor in adult bees (NIVAA)= 3.88% (p= 0.944). It was observed a frequency of Nosema spp. (FN)= 91.96%; infection level of Nosema spp. (NIN)= 133 738 ±156 221 spores/bee. All samples were negative for A. woodi. The results indicate that the presence of V. destructor and Nosema spp. are more frequent in the subregions studied, the levels of infestation of V. destructor and the levels of infection of Nosema spp. are low. However, extreme values that exceed the tolerable limits were found in various communities, which could represent foci of attention before possible dissemination of these pathogens.